Allogeneic adipose‐derived stem cells for the treatment of perianal fistula in Crohn's disease: a pilot clinical trial. (May 2016) - Park, K. J.; Ryoo, S.‐B.; Kim, J. S.; Kim, T. I.; Baik, S. H.; Kim, H. J.; Lee, K. Y.; Kim, M.; Kim, W. H.
Abstract: Aim: Many perianal fistulae in Crohn's disease do not respond to conventional surgical and medical management and recurrence rates are high. The study evaluated the safety and feasibility of allogeneic adipose‐derived stem cells for the treatment of perianal fistula in Crohn's disease. Method: A multicentre, open‐label, dose escalation pilot study was performed. The first three patients (group 1) were administered 1 × 10 7 cells/ml based on the size of the fistula tract. Four weeks later, after which time this dose had been confirmed to be safe, the next three patients (group 2) were administered 3 × 10 7 cells/ml. The end‐point was complete closure at 8 weeks after the injection. Patients who attended for the 8 week assessment were followed for an additional 6 months. Results: There were no adverse events of Grade 3 or 4 severity and no adverse events related to the treatment with allogeneic adipose‐derived stem cells. Two patients in group 1 achieved complete closure of the fistula at month 4 and month 6, and one patient in group 2 achieved complete closure at 8 weeks. The closure was sustained up to month 8 in all three of those patients. Conclusion: These data suggest that allogeneic adipose‐derived stem cells may be a feasible treatment option for perianal fistula in Crohn's disease.